An Adult Kawasaki Disease with Coronary Artery Involvement: A Unique Case Report and Literature Review - FaisalUddin, Mohammed (Cureus, 2019)
Kawasaki disease (KD) is an acute, febrile, vasculitis of mainly large to medium-sized vessels. KD is a self-limited illness of infancy and childhood and 80% of the patients are younger than four years of age with an incidence of 5.6/100,000 in the United States. We present an unusual case of an 18-year-old man with several unique features of KD. He was admitted to the hospital with fever, rash, and arthralgia for one week. KD was among the differentials for fever, rash, and arthralgia. Later all the laboratory diagnosis for bacterial and viral infections including blood and urine culture came out negative and he was further evaluated for KD with electrocardiography (EKG), echocardiography, and angiography which showed myocarditis. Based on typical features of fever, rash, arthralgia, bilateral conjunctival injection, cervical lymphadenopathy, and prominent tongue papillae he was diagnosed with KD.